2009
DOI: 10.1111/j.1744-7917.2009.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of heavy metal tolerance and evolution in invertebrates

Abstract: Following the genomics revolution, our knowledge of the molecular mechanisms underlying defenses against stress has been greatly expanded. Under strong selective pressure many animals may evolve an enhanced stress tolerance. This can be achieved by altering the structure of proteins (through mutations in the coding regions of genes) or by altering the amount of protein (through changes in transcriptional regulation). The latter type of evolution can be achieved by substitutions in the promoter of the gene of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 165 publications
1
78
0
4
Order By: Relevance
“…in volcanic rocks, ores, various deposits created by industrial activity (Sharma and Agrawal, 2005;Florea and Busselberg, 2006). Both biologically necessary and undesirable metals can be toxic for living organisms if they are present in doses which exceed the critical level (Janssens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…in volcanic rocks, ores, various deposits created by industrial activity (Sharma and Agrawal, 2005;Florea and Busselberg, 2006). Both biologically necessary and undesirable metals can be toxic for living organisms if they are present in doses which exceed the critical level (Janssens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…But, part of the explanation can also be that different population traits and strategies have been selected at these two sites, resulting in different population characteristics, hereunder skewed sex ratios. Selection toward tolerant populations has previously been demonstrated in laboratory exposure systems (e.g., Luoma et al, 1983;Klerks and Levinton, 1989;Galletly et al, 2007;Janssens et al, 2009), where for example Klerks and Levinton (1989) found population-level resistance acquired after only one to four generations in an oligochaete cultured in the presence of cadmium. Anthropogenically impacted sediments are however rarely contaminated with single chemicals, and resistance to contaminant mixtures appears to be more difficult to achieve than resistance to single substances Klerks (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Iron, copper, zinc and manganese are classified as essential heavy metals in human diet because they all play significant roles in metabolic processes (Janssens et al, 2009). These metals are also known to help in the growth and production of aquatic life.…”
Section: Introductionmentioning
confidence: 99%